Role of Bronchial Brush Cytology in Diagnosis of Bronchopulmonary Lesions - Jahan, Rukhshana Akhter; Islam, Md Rezaul; Majumder, Samir; Sultana, Rebeka (TAJ: Journal of Teachers Association, 2022)
Bronchial carcinoma is currently the most common cause of cancer-related mortality worldwide. The increasing incidence could be due to increased smoking habits, change in lifestyles, increased environmental pollution, and the availability of different modalities to detect lung cancer. Fibreoptic bronchoscopy was introduced in 1968 to evaluate bronchopulmonary lesions. Since then, various methods for obtaining good specimens have become available apart from sputum. A higher positive rate was obtained from specimens collected by fiberoptic bronchoscope. We aimed to assess the sensitivity and specificity of brushings compared with the biopsy of lung lesions. The study was done on 100 patients, of which bronchial brush cytology was done in all 100 cases, and endobronchial biopsy was carried out in 20 cases. This study showed sensitivity, specificity, positive predictive value, negative predictive value, and accuracy of brushing to be 87.5%, 75%, 85%, 93.13%, and 60%, respectively. TAJ 2022; 35: No-1: 107-115